Prioriza SUS: Proposta para o aperfeiçoamento da gest\~ao do SUS por meio do planejamento, do monitoramento e da avaliaç\~ao da aç\~ao governamental - Fabiola Sulpino Vieira; Luciana Mendes Santos Servo; Sérgio F. Piola; Edvaldo Batista de Sá; Rodrigo Pucci de Sá ce Benevides (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The objective is to analyze problems of the health sector in Brazil, with emphasis on the management of the SUS, aiming at the elaboration of concrete interventions proposals to ensure the population's access to universal, egalitarian and comprehensive healthcare. The methodological framework of public policy analysis was used to examine healthcare problems and propose solutions. The public problem, which is the distance between current and desired situation from the point of view of a relevant actor was defined as "difficulty in timely, effective and equitable access to health care". A problem tree was created, and several causes were identified. This study concentrates in a structural problem of the SUS that was called 'deficient strategic management', which has among its causes "deficient and insufficient planning, monitoring and evaluation processes". Some actions were proposed to face this problem. Next, a public policy forum was held with the participation of SUS researchers, workers, and managers with relevant knowledge on the subject, to discuss the preliminary actions proposal. Contributions from forum participants were incorporated, improving the actions initially proposed and adding a new action to the list of measures suggested as a response to the structural problem under analysis. Finally, it is recommended to evaluate the appropriateness of the solutions suggested in the discussions that may take place under the initiative of the Ministry of Health, with the objective of agreeing on actions that promote planning, monitoring and evaluation in the SUS and, with that, the improvement of its strategic management.
Keywords: I10; I18; 330; Health policy; health management; health policy; planning and management; health planning; health evaluation; Unified Health System